2020
DOI: 10.3390/urbansci4040053
|View full text |Cite
|
Sign up to set email alerts
|

Message Sent, Now What? A Critical Analysis of the Heat Action Plan in Ahmedabad, India

Abstract: To protect public health, heat-related policies are increasingly being adopted by city authorities to address the unequal impact of heatwaves. Ahmedabad’s Heat Action Plan (HAP) is an acclaimed and successful policy response in India and beyond. While the pilot evaluation of the initiative suggests that almost a thousand deaths were avoided annually after its implementation, it is not yet clear whose lives were saved, and to what extent this statistic was due to the HAP, rather than other factors. By reviewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(70 reference statements)
0
5
0
Order By: Relevance
“… 37 38 In Ahmedabad, India, the citywide implementation of a heat warning system coupled with a widespread communication effort led to a decrease in the number of heat-related deaths reported to the hospital. 39 A quasi-experimental study from Chongqing, China, tested a broader set of interventions, including a heat-specific healthcare network, early warning system and preparation, a 24-hour health helpline and doctors' training on heat illnesses. The study found a significant improvement in the incidence of heat-related illnesses in the subset of rural populations measured through two surveys 1 year apart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 38 In Ahmedabad, India, the citywide implementation of a heat warning system coupled with a widespread communication effort led to a decrease in the number of heat-related deaths reported to the hospital. 39 A quasi-experimental study from Chongqing, China, tested a broader set of interventions, including a heat-specific healthcare network, early warning system and preparation, a 24-hour health helpline and doctors' training on heat illnesses. The study found a significant improvement in the incidence of heat-related illnesses in the subset of rural populations measured through two surveys 1 year apart.…”
Section: Discussionmentioning
confidence: 99%
“…Further, targeted interventions focusing on high-risk groups such as the elderly and those with known chronic medical conditions through door-to-door checks, focused health messaging and close follow-up with primary physicians have also shown a significant reduction in mortality rates 37 38. In Ahmedabad, India, the citywide implementation of a heat warning system coupled with a widespread communication effort led to a decrease in the number of heat-related deaths reported to the hospital 39. A quasi-experimental study from Chongqing, China, tested a broader set of interventions, including a heat-specific healthcare network, early warning system and preparation, a 24-hour health helpline and doctors' training on heat illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…85 Heat health warning systems have been shown to be effective in high-income countries, 86 and ongoing work shows promising evidence from LMICs. 87,88 However of note, this evidence relates to evaluation of impact on the rate of mortality in the general population and to date there have been no evaluations of the impact of these F I G U R E 2 Hypothesised pathophysiological pathways of the impact of heat on the placenta and the fetus. Abbreviations: ER, endoplasmic reticulum; HSP, heat-shock proteins.…”
Section: U R R E N T Gu I Da Nc E : R E Duci Ng Th E H E At R Isk I N...mentioning
confidence: 99%
“…Public health action to reduce the health impacts of heat (visualised in Figure 3) can be broadly considered as (1) public health messaging and awareness/individual behaviour change, (2) community‐level interventions and (3) healthcare provider interventions 85 . Heat health warning systems have been shown to be effective in high‐income countries, 86 and ongoing work shows promising evidence from LMICs 87,88 . However of note, this evidence relates to evaluation of impact on the rate of mortality in the general population and to date there have been no evaluations of the impact of these action plans for heat‐related morbidity or pregnancy‐related complications.…”
Section: Current Guidance: Reducing the Heat Risk In Pregnancymentioning
confidence: 99%
“…These strategies may include using green spaces, light colored pavements or roofs, and increasing vegetation or tree canopies. Adaptation solutions may involve establishing early heat warning systems, designing cooling centers, creating heatwave action plans, and preparing healthcare providers for heatwave events (Boyson et al, 2014;Ebi et al, 2020;Nastar, 2020;Smoyer-Tomic & Rainham, 2001). Successful research, solution development, and application of solutions require interdisciplinary collaboration among scientists, urban planners, policy makers, health care systems, and communities.…”
mentioning
confidence: 99%